Hydrothermal Carbonization of Cattle Paunch Waste: Process Conditions and Product Characteristics. Issue 6 (December 2020) - Saverettiar, Gwenella; Li, Dan; Gross, Amit; Ho, Goen
Graphical abstract: Highlights: HTC was used to treat cattle paunch waste into hydrochar. HTC conditions (time, temperature and moisture) were varied. Fuel properties of hydrochar improved after carbonization. Liquid product contained significant levels of N, C and K. A small fraction of hydrochar combustion energy can provide HTC input energy. Abstract: In abattoir operation, paunch waste can present a major problem when flushed with water and discharged. Collected and processed separately, it provides a means of reusing organic carbon and nutrients. Hydrothermal carbonisation (HTC) is a means to process the waste that overcomes some problems of composting and anaerobic digestion. Experiments were conducted to investigate HTC of cattle paunch waste to hydrochar under different conditions. The fuel characteristics of hydrochar were tested for the potential in electricity generation and the nutrient concentrations of liquid were analysed for soil fertilization. The carbon content of paunch increased (∼15%) after HTC. It was also reflected in its increasing calorific value. The changes in the H/C and O/C ratios, analysed using the van Krevelen diagram, showed that the fuel properties of hydrochar improved noticeably after carbonisation. The TOC and TN concentrations in the liquid changed significantly with increasing temperature and time. With increasing moisture, the nutrient concentrations decreased, because of dilution effect. The liquid product contained significant levels of N, C and K; but may need suitable dilution before applying as a fertiliser. An energy balance showed that a fraction (<45%) of the hydrochar combustion energy was required to provide the input energy for HTC.